Vocational education and training in Europe, 1995-2035 : scenarios for European vocational education and training in the 21st century - (:unkn) unknown (Publications Office of the European Union, 2020)
“This synthesis report summarises the findings of the Cedefop project The changing nature and role of vocational education and training in Europe (2016-18). Project research covered the 28 EU Member States as well as Iceland and Norway, aiming to take a step back and paint a comprehensive picture of VET developments in Europe, identifying challenges as well as opportunities. The summary shows that European vocational education and training (VET) varies between countries and is changing in a number of fundamental ways. European VET is becoming more diverse in its programmes and qualifications and also expanding into higher levels, challenging the perception of higher education as exclusively academically oriented. In some countries, this reflects a step towards making lifelong learning a reality; in others, traditional VET is coming under pressure from declining youth cohorts and a growing preference for general education and training. Such negative developments can be seen as a forewarning of future challenges.“ (editor; BIBB-Doku)
Keywords: S System beruflicher Bildung; S 2.3 Berufsbildungspolitik; I 2.2 Europa; 370; 330; Berufsbildung; Berufsbildungssystem; Berufsbildungspolitik; EU-Bildungspolitik; Zukunftsperspektive; Szenario; EU-Staat; Europa; 1995-2035